2020
DOI: 10.1126/sciadv.aax6969
|View full text |Cite
|
Sign up to set email alerts
|

The energy landscape of −1 ribosomal frameshifting

Abstract: Maintenance of translational reading frame ensures the fidelity of information transfer during protein synthesis. Yet, programmed ribosomal frameshifting sequences within the coding region promote a high rate of reading frame change at predetermined sites thus enriching genomic information density. Frameshifting is typically stimulated by the presence of 3′ messenger RNA (mRNA) structures, but how these mRNA structures enhance −1 frameshifting remains debatable. Here, we apply single-molecule and ensemble appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 49 publications
5
63
0
Order By: Relevance
“…2D, F) were 5-and 7-fold shorter, respectively, than those measured in ribosomes programmed with dnaX_Slip mRNA. In agreement with previously published results (Caliskan et al, 2017;Chen et al, 2014;Choi et al, 2020;Kim et al, 2014), our data demonstrate that dnaX FSS positioned near the mRNA channel entrance strongly inhibits mRNA/tRNA translocation ( Fig. 2E-F).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…2D, F) were 5-and 7-fold shorter, respectively, than those measured in ribosomes programmed with dnaX_Slip mRNA. In agreement with previously published results (Caliskan et al, 2017;Chen et al, 2014;Choi et al, 2020;Kim et al, 2014), our data demonstrate that dnaX FSS positioned near the mRNA channel entrance strongly inhibits mRNA/tRNA translocation ( Fig. 2E-F).…”
Section: Resultssupporting
confidence: 93%
“…(i) slippage of the single P-site tRNA when the A site remains vacant, or (ii) frameshifting of both P-site and A-site tRNAs when two tRNAs are bound to the ribosome (Caliskan et al, 2017;Korniy et al, 2019). Our finding that the dnaX FSS slows the rate of ribosome translocation by ~10-fold is also in excellent agreement with a number of previous reports (Caliskan et al, 2017;Chen et al, 2014;Choi et al, 2020;Kim et al, 2014;Kim and Tinoco, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As the C-to-U transition is not a frequent change introduced by the polymerase, it is possible that it originates from RNA editing by a cytosine deaminase 35,42,43 . Biophysical single-molecule assays and kinetics studies on ensembles revealed how the interplay between the conformational plasticity of RNA-inducing frameshifting structures and the dynamics of the ribosome play a critical role in the -1 PRF mechanism [50][51][52][53][54] . Interestingly, the type 1 change results in the substitution of a G-C Watson-Crick pair in the functional core of the SARS-CoV-2 pseudoknot with a wobble G-U pair.…”
Section: Discussionmentioning
confidence: 99%